Invasive fungal infections in children with acute lymphoblastic leukaemia: Results from four Australian centres, 2003‐2013. Issue 10 (16th July 2019) - Wang, Stacie S.; Kotecha, Rishi S.; Bernard, Anne; Blyth, Christopher C.; McMullan, Brendan J.; Cann, Megan P.; Yeoh, Daniel K.; Bartlett, Adam W.; Ryan, Anne L.; Moore, Andrew S.; Bryant, Penelope A.; Clark, Julia; et al.
Abstract: Background: Invasive fungal infections (IFI) are an important complication of acute lymphoblastic leukaemia (ALL) treatment. Our study describes the prevalence and outcomes of IFI in children with ALL. Methods: IFI episodes in children with primary or relapsed ALL, identified for The Epidemiology and Risk Factors for Invasive Fungal Infections in Immunocompromised Children study, were analysed. IFI were classified according to European Organization for Research and Treatment of Cancer/Invasive Fungal Infections Cooperative Group criteria with a 'modified‐possible' category included. Results: A total of 123 IFI episodes in 119 patients with ALL were included. A proven, probable, possible and modified‐possible IFI was diagnosed in 56 (45.5%), 22 (17.9%), 39 (31.7%) and six (4.9%) episodes, respectively. The prevalence was 9.7% (95% confidence interval [CI] 8‐11.4%) overall and 23.5% (95% CI 14.5‐32.5%) for relapsed/refractory ALL. For non‐relapsed ALL, the IFI prevalence was significantly higher for children with high‐risk compared to standard‐risk ALL (14.5% vs 7.3%, P = .009), and IFI were more common during induction, consolidation and delayed intensification phases. Mould infections occurred more frequently than non‐mould infections. Thirteen children (10.9%) died within 6 months of IFI diagnosis with five deaths (4.2%) attributable to an IFI. Conclusions: IFI is more common in children with high‐risk ALL and in relapsed disease. Overall survival was encouraging, with IFI contributing to very few deaths.